EDUCATIONAL PROGRAMM TO IMPROVE COPING MECHANISMS OF PARENTS WITH CHILDREN WITH CONGENITAL HEART DISORDERS - Runtunuwu, Felorensiana; Musharyanti, Lisa (Jurnal Keperawatan Respati Yogyakarta, 2022)
Congenital heart disease (CHD) is one of the most common congenital abnormalities in children with a chronic course of disease. CHD almost always causes problem psychologically either for patients and their families. Education about CHD in children addressed to their parents and caregivers could help to overcome the emotional problems that arise while caring for children with CHD. This study was at a time to review the educational programm that can be used to improve the parental coping mechanism of children with CHD. This study is a literature review sourced from PubMed, Google Scholar andScience Directdatabases, with inclusion criteria as follows: articles published in 2015-2020, available in full text and published in Indonesian and English. Our results found 169 articles, of them only 3 that met the inclusion criteria. Implementation of empowerment-based education program was proved to improve the knowledge, parenting behavior, and self-efficacy of parents and caregivers of children with CHD. Education with audiovisual media such as photos related to diagnostic procedures could be an important first step. The level of parental anxiety was lower in the intervention group than the control group (M=63, SD=3.5 vs M=70, SD=2.8). Module-based and workshop-based intervention programs such as the Congenital Heart Disease Intervention Program (CHIP)-Family intervention or education with evidence-based Families coping programs have been shown to improve mental health and coping mechanisms for parents of children with CHD. Nursing education using various media has been proven to improve the coping mechanisms of parents of children with CHD Keywords: Education; Media; Parents; Family; Coping Mechanisms; CHD